2007
DOI: 10.1186/bcr1660
|View full text |Cite
|
Sign up to set email alerts
|

Association of estrogen receptor-α and progesterone receptor A expression with hormonal mammary carcinogenesis: role of the host microenvironment

Abstract: Introduction Medroxyprogesterone acetate (MPA) induces estrogen receptor (ER)-positive and progesterone receptor (PR)-positive ductal invasive mammary carcinomas in BALB/c mice. We sought to reproduce this MPA cancer model in C57BL/6 mice because of their widespread use in genetic engineering. Within this experimental setting, we studied the carcinogenic effects of MPA, the morphologic changes in mammary glands that are induced by MPA and progesterone, and the levels of ER and PR expression in MPA-treated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 60 publications
0
16
0
1
Order By: Relevance
“…However, there is to our knowledge no study regarding antiprogestin-resistance in breast cancer. The main reason is that despite all the increasing evidence relating PR with proliferative signals in the mammary gland [4,6,46], there are very few studies focused on unraveling the role of PR in breast cancer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there is to our knowledge no study regarding antiprogestin-resistance in breast cancer. The main reason is that despite all the increasing evidence relating PR with proliferative signals in the mammary gland [4,6,46], there are very few studies focused on unraveling the role of PR in breast cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Progesterone has been shown to be required for the proliferation of mammary glands [4][5][6] and mammary carcinomas [7,8]. The synthetic progesterone, medroxyprogesterone acetate (MPA) behaves experimentally as a mammary-specific carcinogen [9][10][11], and most importantly, in combination with E 2 , it is associated with an increased risk of breast cancer development [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Like the uterus (5), phenotypic variation in the responsiveness of the adult mammary gland to E 2 , during both normal and pathological conditions, including tumor formation, was reported long ago (6, 16, 17). In addition, genetic control of mammary development (18), response to hormones (19), and ductal morphology (20, 27) have been observed. Blair et al (17) observed marked variation in mammary alveolar development induced by treatment with E 2 and progesterone in several strains of male mice, including B6 and C3H.…”
Section: Mammary Glandmentioning
confidence: 99%
“…Therefore, many of the studies investigating the strain differences in the response of the mammary gland to E 2 that were published before 1999 were either confounded by the presence of MMTV or were designed to investigate the mammary response to E 2 in the context of MMTV (7,16,17,(22)(23)(24)(25)(26). More recent reports have confirmed that, even in the absence of MMTV, the response of the mammary gland to E 2 and progesterone (19) and to environmental estrogens (27,28) is genetically controlled.…”
Section: Mammary Glandmentioning
confidence: 99%
“…In this report, we validated the effectiveness of our HMSP by comparing the effect on HD and HI tumor growth with commercially available sc MPA pellets or daily injections of MFP solution, that have proven to be effective in inducing or inhibiting tumor growth, respectively [13]. Pg HMSP induced lobular differentiation in mammary glands from ovariectomized mice [30], [31]. We found that HMSP induced similar biological effects on tumor growth and mammary gland histology as the other validated methods used to administer steroids, demonstrating that this is an effective method for delivering steroids to mice.…”
Section: Discussionmentioning
confidence: 91%